Capacitively coupled hydrogen plasmas sustained by tailored voltage waveforms: vibrational kinetics and negative ions control. (26th June 2017) - Diomede, P; Bruneau, B; Longo, S; Johnson, E; Booth, J-P
Abstract: A comprehensive hybrid model of a hydrogen capacitively coupled plasma, including a detailed description of the molecular vibrational kinetics, has been applied to the study of the effect of tailored voltage waveforms (TVWs) on the production kinetics and transport of negative ions in these discharges. Two kinds of TVWs are considered, valleys-to-peaks and saw-tooth, with amplitude and slope asymmetry respectively. By tailoring the voltage waveform only, it is possible to exert substantial control over the peak density and position of negative ions inside the discharge volume. This control is particularly effective for saw-tooth waveforms. Insight into the mechanisms allowing this control is provided by an analysis of the model results. This reveals the roles of the vibrational distribution function and of the electron energy distribution and their correlations, as well as changes in the negative ion transport in the electric field when using different TVWs. Considering the chemical reactivity of H − ions, the possibility of a purely electrical control of the negative ion cloud in a reactor operating with a feedstock gas diluted by hydrogen may find interesting applications. This is the first study of vibrational kinetics in the context of TVWs in molecular gases.